Tari “Mahelo Nan Ado” Terinspirasi dari Kegiatan Mamukek di Kecamatan Lengayang Kabupaten Pesisir Selatan - Ressia Aulia Putri; Rasmida Rasmida; Ali Sukri; Kurniadi Ilham (Universitas Serambi Mekkah, 2026)
The dance work “Mahelo Nan Ado” is inspired by the traditional mamukek activity in Lengayang District, Pesisir Selatan Regency. The mamukek or maelo pukek tradition is a method of catching fish practiced by coastal fishermen using large, long nets and ropes, which are cast from the shore to catch fish. This activity served as the source of inspiration for the choreographer to create a group dance that interprets the maelo pukek fishing activity. The central issue explored in this work is the togetherness and cooperation among the fishermen, as well as the gratitude they feel for the harvest they receive. The theoretical foundation used in the creation process is macro sociology, which relates to large-scale and long-term social processes that underlie the division of individuals into various groups. The choreographic method applied in this work follows the model developed by Alma M. Hawkins, as translated by Y. Sumandiyo Hadi, which includes field observation, literature study, exploration, movement arrangement, improvisation, composition, and evaluation. The choreography is structured into three parts: a calm atmosphere, tension, and joy mixed with solemnity. The piece is performed by seven female dancers and was staged on July 17, 2025, at the Boestanul Arifin Adam Auditorium, Indonesian Institute of the Arts (ISI) Padangpanjang.